Macrophage hypoxia signaling regulates cardiac fibrosis via Oncostatin M - Hajime Abe (Nature Portfolio, 2019)
Fibrosis is a hallmark of several cardiac pathologies and its underlying mechanisms are still poorly defined. Here the authors show that macrophage hypoxia signaling following transverse aortic constriction in mice suppresses the activation of cardiac fibroblasts by secreting oncostatin M.